Deciphering the relationship between objective and subjective aspects of recollection in healthy aging. Issue 3 (15th March 2020) - Folville, Adrien; D'Argembeau, Arnaud; Bastin, Christine
ABSTRACT: Although healthy aging has been related to a decline in recollection as indexed by objective measures, the subjective experience of recollection sometimes remains stable. To date, however, these age-related differences have only been examined using aggregated data across trials. In the current study, we investigated the relationship between subjective and objective measures of recollection on a trial-by-trial basis to determine whether the magnitude of this relationship was similar in young and older adults. Young and older participants were presented with pictures that were associated with descriptive labels at encoding. At retrieval, they were cued with the labels and were asked to rate the vividness of their memory for the associated picture and to recall as many details of the picture as possible. On average, older adults assigned higher vividness ratings but recalled fewer episodic details than young adults. Mixed-effects modelling revealed that the relationship between subjective (vividness) and objective (number of recalled details) recollection across trials was stronger in young than in older participants. These findings provide evidence that older adults not only retrieve fewer episodic details but also rely on these details to a lesser extent than young adults for judging the subjective quality of their memories.